Analisis Peramalan Permintaan Consumable Material Pada Divisi Rekayasa Umum PT XYZ dengan Metode Time Series Menggunakan Software POM-QM - Muhammad Zainur Roziqin; Rr. Rochmoeljati (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Forecasting is an analytical method that involves calculations with both qualitative and quantitative approaches, which aim to estimate future events. Every company, including PT XYZ, needs an inventory control system to achieve optimal inventory levels. The problem that exists in the scope of supplying consumable materials in the General Engineering Division of PT XYZ is that every month there is often a shortage of consumable materials, especially in the 3 most frequently used consumable materials, namely UK 4'' x 6 Grinding Stones, DIA Roll Brushes. 1” X 4 ”L, and Wire Rod DIA. 1.2 MM. This research applies the Time Series Simple Moving Average and Weighted Moving Average methods as an approach to analyze historical data and forecast future material demand. To support this analysis, POM-QM software is used which has the ability to process and process time series data effectively. After the calculation is carried out, the results of UK 4 'x 6 Grinding Stone forecasting using the Weighted Moving Average method produce a 13th period forecast of 156 pcs. Forecasting Brush Roll DIA. 1 “X 4 ”L using the Weighted Moving Average method resulted in a 13th period forecast of 29 pcs. While forecasting Wire Rod DIA. 1.2 MM using the Simple Moving Average method resulted in a 13th period forecast of 630 kg.